Balance of Payments an Aspect of Macroeconomic Management : A Case Study of Malaysia in the Eighties and Nineties - Chandran, Krishnan Nair (1998)
This study focuses on recent trends in the Malaysia’s Balance of Payments and their implications. A comparison of current account deficits between the period within the 5th and 6th Malaysia Plans has been made. The main balance of payments issues of the late eighties and the nineties have been discussed while emphasizing the declining competitiveness of Malaysia’s traditional exports, the high import content in both consumption and development expenditure and continuing high invisible payments abroad. The export trend is thoroughly examined. Finally, some recommendations to reverse the current account deficit are made in which the major ones include greater fiscal discipline, export productivity enhancement, more aggressive marketing strategies and measures to counter the currency crisis.